1999
DOI: 10.1002/etc.5620180229
|View full text |Cite
|
Sign up to set email alerts
|

Benthic invertebrate metals exposure, accumulation, and community‐level effects downstream from a hard‐rock mine site

Abstract: Abstract-This study quantitatively evaluated the relationships among As, Co, and Cu concentrations in exposure media (surface water, sediment, and aufwuchs), As, Co, and Cu concentrations in aquatic macroinvertebrates, and invertebrate community structure in a mine-affected stream. Concentrations of As, Co, and Cu were significantly elevated in both exposure media and invertebrate tissue downstream from the mine. Copper in invertebrates was significantly correlated only with Cu in aufwuchs, and Co in invertebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(43 citation statements)
references
References 39 publications
6
36
1
Order By: Relevance
“…Chadwick et al [40] also found low densities of Optioservus downstream from a mine input to a Rocky Mountain stream. Our findings are also contrary to those of Beltman et al [4] who observed that early instars of Optioservus spp. may be adversely affected by Cu concentrations as low as 5 g/L.…”
Section: Macroinvertebrate Metric Responsescontrasting
confidence: 99%
See 4 more Smart Citations
“…Chadwick et al [40] also found low densities of Optioservus downstream from a mine input to a Rocky Mountain stream. Our findings are also contrary to those of Beltman et al [4] who observed that early instars of Optioservus spp. may be adversely affected by Cu concentrations as low as 5 g/L.…”
Section: Macroinvertebrate Metric Responsescontrasting
confidence: 99%
“…Similar observations on the two macroinvertebrate taxa were reported by Clements et al [33] and Beltman et al [4]. Studies by Plafkin et al [34] and Barbour et al [35] found Ephemeroptera, Plecoptera, and Trichoptera richness to be sensitive variables to a variety of stressors including metal contaminants.…”
Section: Macroinvertebrate Metric Responsessupporting
confidence: 80%
See 3 more Smart Citations